2014
DOI: 10.2460/ajvr.75.6.544
|View full text |Cite
|
Sign up to set email alerts
|

Use of an inverse dynamics method to describe the motion of the canine pelvic limb in three dimensions

Abstract: Knowledge of the 3-D movement of the pelvic limb can be used to better understand its motion, moment, and energy patterns in healthy dogs and provide a referent with which gaits of dogs with pelvic limb injuries before and after surgical repair or rehabilitation can be compared and characterized. This information can then be used to guide decisions regarding treatment options for dogs with pelvic limb injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 18 publications
1
24
1
Order By: Relevance
“…26 Briefly, a 60-Hz, 4-camera, 3-D motion capture system a was used to collect kinematic data. 26 Briefly, a 60-Hz, 4-camera, 3-D motion capture system a was used to collect kinematic data.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…26 Briefly, a 60-Hz, 4-camera, 3-D motion capture system a was used to collect kinematic data. 26 Briefly, a 60-Hz, 4-camera, 3-D motion capture system a was used to collect kinematic data.…”
Section: Methodsmentioning
confidence: 99%
“…26 Briefly, kinetic data were processed by custom software, c and kinematic data were processed by a motion analysis system. 26 Briefly, kinetic data were processed by custom software, c and kinematic data were processed by a motion analysis system.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The center of rotation of the stifle joint was defined as the location between medial and lateral femoral condyle; this approximation was based on definitions from a study which also used a rigid body model of a canine pelvis and pelvic limb (Headrick et al, 2014). Although a reasonable approximation, it has been demonstrated that the location of the center of rotation of the stifle varies as a function of flexion/extension in dogs (Ireland et al, 1986).…”
Section: Joint Kinematicsmentioning
confidence: 99%
“…The center of rotation of the tarsus joint was defined as the location between medial and lateral malleolus; this approximation was based on definitions from a study which also used a rigid body model of a canine pelvis and pelvic limb (Headrick et al, 2014). To the author's knowledge, no studies have been done to model abduction/adduction or internal/external rotation in the tarsal joint of dogs.…”
Section: Joint Kinematicsmentioning
confidence: 99%